Use of open data as a tool for successful lean management in public services: Evidence from Greece - Michail K. Angelopoulos; Yannis A. Pollalis (SPOUDAI - Journal of Economics and Business, 2020)
Our modern society and economy moves toward a knowledge-based and service-oriented global world. With the increase of mobile network, mobile devices, and internet of things, many industries, including government departments, private firms, and research communities, offer more transparency through releasing data. Open datasets can be used in smart city services, financial monitoring, decision support systems and other applications, becoming a first priority for governments. In the EU, the public sector is one of the most data-intensive sectors, it holds vast amounts of data, and can be readily and widely accessible sometimes under non-restrictive conditions. As a result, fundamental changes are taking place on how governments operate. One of the major challenges is to operate in a connected environment, engage stakeholders and solve societal problems by utilizing new methods, tools, practices and governance models while reducing the costs. Such changes are under the umbrella of 'lean government' where governments aim at reducing the complexity of the public sector by simplifying and streamlining organizational structures and processes. In this paper, we conducted a research on the current state of open data in Greece and how we apply lean management for public industries.
Keywords: H0; M0; M1; 330; open data; lean management; public industries; government